Spectrometric elucidation of intermediates in asymmetric transfer hydrogenation of ketones catalyzed by complex of ruthenium (II) and isosorbide-based ligand - Duy, Huynh Khanh (Vietnam Journal of Chemistry, 2016)
The use of electrospray ionization mass spectrometry for the detection of the intermediate species involved in the ruthenium(II)/β-amino-alcohol derived from isosorbide reduction of ketones to alcohols is described. The formation of active complex of ruthenium (II) for catalyzing the asymmetric transfer hydrogenation of ketones was observed from 1H-NMR spectra. From high resolution mass spectra, peaks of group of isotopes allow to conform the existence of active species of ruthenium (II) in the presence of isosorbide-based ligand. The recorded high resolution mass spectra when following the typical protocol for the asymmetric transfer hydrogenation of acetophenone confirmed an involvement of the active complex mono-hydride ruthenium in the catalytic circle. As a result, high resolution mass spectra in research on catalytic mechanism can be therefore employed as an alternative tool for studying catalytic mechanism. Keywords. Asymmetric catalysis, isosorbide, asymmetric transfer hydrogenation